The Principle Of The Rule Of Law And Increasing The Legal Activity Of Young People - Saitkasimov Akbar Isaxanovich (Peerian Journals Publishing, 2024)
This article explores the crucial role of legal activism in fostering social stability and the active participation of young people in the realization of the rule of law within a legal state. It highlights how law serves as the foundational regulatory framework that ensures the protection of individual rights and societal stability. The article discusses the importance of legal awareness among young people and their proactive involvement in societal processes, including state and public affairs, as a means to strengthen social cohesion and contribute to the overall development of the state. It also emphasizes the need for systemic support in promoting youth legal engagement, such as through state initiatives and programs that create opportunities for young people to engage in legal processes and contribute to societal progress. The article outlines key tasks to enhance youth legal activism, including continuous social integration, governmental and organizational support, and addressing negative factors that hinder legal participation. Ultimately, it stresses the need to develop a strong legal culture among youth to ensure a stable and prosperous future for both individuals and society as a whole.
Keywords: society; state; Constitution; law